2014
DOI: 10.2478/bvip-2014-0075
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Heart Rate in Primitive Horses and Their Relatives as an Indicator of Stress Level, Behavioural Conduct Towards Humans and Adaptation to Living in Wild

Abstract: The aim of the study was to evaluate the possibility of using heart rate (HR) as a metric parameter that can be used for the characterisation of behaviour of primitive horses and their relatives, related to reactions to the stress resulting from the contact with humans and adaptation to living in various conditions, including natural environment. This characterisation served the authors to expand the knowledge of such behaviour of primitive horses, and to assess the impact of the environmental and genetic fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…1), which suggests that these procedures are much less comfortable for the horse. Pluta and Osiński [2014] also claimed that hooves cleaning may be more stressful for the horses than other grooming procedures. Present study shows a significant influence of horse sex on the heart rate level during bridling and legs raising.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…1), which suggests that these procedures are much less comfortable for the horse. Pluta and Osiński [2014] also claimed that hooves cleaning may be more stressful for the horses than other grooming procedures. Present study shows a significant influence of horse sex on the heart rate level during bridling and legs raising.…”
Section: Methodsmentioning
confidence: 99%
“…1990, Jezierski et al 1999, Pluta and Osiński 2014, Topczewska 2014. The research carried out by Budzyński et al [1990] analysed the nervous excitability of Konik polski horses and Hucul horses during fearfulness test and sound test.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 1934 horses were used across all 45 studies, with a mean of 44 and median of 20, ranging from 3 to 339. One study, which observed three herds of undomesticated horses [37], did not report the number of equine participants.…”
Section: Article Characteristics 321 Study Populationsmentioning
confidence: 99%
“…A nervous mood can be transmitted from humans to horses under handling and riding conditions [9]. Voice [10][11][12], posture [13,14], facial expression [15,16], autonomic signals [17][18][19], hormones [20][21][22][23] and pheromones [24] might be used to fruitfully describe and characterize the emotional content [25]. Non-verbal communication between human and horse was also investigated in [26,27].…”
Section: Introductionmentioning
confidence: 99%